Cryopreservation of ram semen: baicalein efficiency on oxidative stress, chromatin integrity, viability and motility post thaw - Avdatek, Fatih; Güngör, Şükrü; Gülhan, Mehmet Fuat; İnanç, Muhammed Enes; Olğaç, Kemal Tuna; Denk, Barış; Yeni, Deniz; Taşdemir, Umut (Frontiers in Veterinary Science, 2024)
Baicalein (B) has potential antioxidant properties, but it has not been tested as a ram semen extender. This study aimed to assess the impact of B on various semen parameters and determine its potential influence on semen quality after the freeze-thawing process. During the breeding season, ejaculates were obtained from four rams with the aid of an artificial vagina. The collected mixed sperm semen samples were divided into four groups: control (C; 0), B0.5 (0.5 mM), B1 (1 mM), and B2 (2 mM). After semen extension, the samples were loaded into 0.25 mL straws and stored for 2 hours at 4°C prior to freezing in liquid nitrogen vapor and thawed in a water bath at 37°C. Among the groups, B0.5 demonstrated the highest progressive motility results, while B1 and B2 exhibited reduced motility (p<0.05). In terms of high mitochondrial membrane potential, plasma membrane and acrosome integrity, and viability, B0.5 showed significantly superior outcomes to the other B groups (p<0.05), although it was not significantly better than C. B1 displayed the highest plasma membrane integrity levels (p<0.05). Notably, B2 displayed the lowest total antioxidant status levels among the groups (p<0.05). The findings of this study suggested that the in vitro spermatological characteristics of ram spermatozoa such as progressive motility and chromatin integrity can be protected from the freeze-thawing process by using the 0.5 mM dose of baicalein as a semen extender. The treatment of sperm freezing might benefit from further in-depth research on the role of B in the improvement of cryoinjury and its underlying processes.